Effect of Dietary Chromium Supplementation on Growth Performance, Rumen Fermentation Characteristics and Some Blood Serum Units of Fattening Dairy Calves under Heat Stress - Soltan, M.A.; Almujalli, A.M.; Mandour, M.A.; Abeer, M. El-Shinway (Pakistan Journal of Nutrition, 2012)
Twenty four fattening dairy calves were assigned to investigate the effect of dietary Chromium (Cr) supplementation (0 or 3 mg Cr/head/day from organic preparation) on the growth performance and rumen fermentation characteristics as well as on some blood serum parameters under heat stress (35-40°C). Chromium supplementation significantly (p<0.05) increased total feed intake across the whole experimental period by about 10% when compared with the control. Moreover chromium supplementation improve body weight at the end of the experiment, weight gain and feed conversion ratio across the whole experiment by about 7.5%, 13% and 2.7% respectively when compared with the control. Serum insulin concentration increased whereas cortisol concentration decreased, when compared with the control group. Also Cr supplementation showed a trend towards improving rumen fermentation characteristics. It could be concluded that dietary Cr supplementation at level of 6 mg/head/day may offer a potential protective management practice to lessen the effect of heat stress in fattening dairy calves.